JENIS - JENIS TUMBUHAN PAKU (Pterydophyta) DI SEPANJANG JALAN KAMPUS UNIVERSITAS PASIR PENGARAIAN MENUJU PEMDA ROKAN HULU - Akbar, Ali; Ade, Filza Yulina; Afniyanti, Enny (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
Theaims of thisstudy was to determine the species of ferns along the campus road Pasir Pengaraian Universitytoward the Local Governmentof Rokan Hulu Regency. Results showed there were 7 families and 10 species of fernsCyclosorus interruptus, Davallia denticulata, D. solida, Drynaria quersifolia, D. rigudula, Gleichenia linearis,Neprholepis bisserata, N. falcata, Lygodium flexuosum dan Selaginella doederleinii.